Ensino superior e confessionalidade: Uma análise da universidade presbiteriana Mackenzie e da disciplina ética e cidadania com Base na teoria da construção da personalidade Moral de josep maria puig. - BORGES, Inez Augusto (2006)
All education, in some way, is confessional, and basically all occidental universities were created in a Christian context. The Universidade Presbiteriana Mackenzie, as a confessional institution, identified with the reformed Christians values and principles, has been trying to express this identity and, this way, contributing for the integral education of its students, using, among others strategies, the subject "Ethics and Citizen" included in all undergraduates courses. Starting from articulation of different knowledge's fields, among them Psychology, Education, Religion, Ethics and Moral this thesis is a investigation about the relationship between confessional higher education and the construction of undergraduate's moral personality in Universidade Presbiteriana Mackenzie and the contribution of the Ethics and Citizen's contribution for this process. The goal is to face the issues of the institution of higher education's mission in the context of the global world and more and more secularized, seeking for the human formation in the citizen dimension which emphasizes the responsibility and the social compromise. The basic assumption for the research is the possibility to contribute for the construction of the undergraduate's moral personality, considering that, especially in the educational approach, all human kind is unconcluded and indeterminate and is not complete when they come to university and will not be complete when they will leave it. (AU)